Implementation of Community Activities Restrictions During The Covid-19 Pandemic in Criminal Law Perspective - Rahim, Rohani Abdul; Mohammad, Mohammad; Rohaya, Nizla; Wasitaatmadja, Fokky Fuad (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Minister of Transportation Regulation Number 25 of 2020 on Transportation Control during the Idul Fitri Homecoming Year 1441 Hijri in the context of Preventing the Spread of COVID-19. This Regulation of the Minister of Transportation Number 25 of 2020 regulates the transportation system during the Large-Scale Social Restrictions (PSBB) implementation, especially related to the 2020 Idul Fitri Homecoming. The formulation of the problem in this study: first, how could the elements of actions be categorized as violations of criminal law norms? second, could the violation of the prohibition of homecoming be categorized as a violation in the criminal law?. The purpose of this study is to find out that violations of the homecoming ban have met the elements that can be categorized as violations of criminal law norms. The research method used normative legal research for this research and used the Theory of Legal Effectiveness for the theory. This study concludes that: First, an act that can be categorized as a violation of criminal law, then there must be elements of a criminal act, both from a theoretical and legal point of view. Second, that the Ministerial Regulation (Permen) cannot contain criminal provisions.